Inventory theory, mode choice and network structure in freight transport - Combes, François; Tavasszy, Lóránt A. (European Journal of Transport and Infrastructure Research, 2016)
In passenger transport, hub-and-spoke networks allow the transportation of small passenger flows with competitive frequencies, in a way that direct line networks cannot. Equivalently, in freight transport, it can be expected that small shipper-receiver flows of high added value commodities transit through hub and spoke networks, while larger shipper-receiver flows of less expensive commodities are transported directly, without transhipment. The objective of this paper is first to present an analytical model, based on inventory theory, explaining how for a given commodity flow, the organisation of freight transport operations is closely related to the characteristics of the shipper-receiver relationship; second to assess empirically this model. Special emphasis is put on the number of transhipments in the transport operation, as an indication of organisation of the transport operations. The theoretical model is a simplified microeconomic model, built on principles of inventory theory. The empirical assessment of this model is based on the French shipment survey ECHO, which provides both the details of the transport operation and of the shipper-receiver relationships. With this database, we first provide a straightforward, graphical verification of the prediction of the theoretical model; secondly, we estimate it econometrically.